2018
DOI: 10.3164/jcbn.18-26
|View full text |Cite
|
Sign up to set email alerts
|

Covalent adduction of endogenous and food-derived quinones to a protein: its biological significance

Abstract: There are many chemically reactive compounds, including quinone, in living systems and also food. Even after the ingestion of food polyphenols, quinones derived from catechol moieties could form endogenously in the body. Dopaquinone, dopamine quinone, estrogen-derived quinones, tryptamine-4,5-dione, and ubiquinone are examples of an endogenous quinone. These indicate that quinone is ubiquitously formed or present in living systems and food. Quinones can induce a variety of hazardous effects and also could have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 74 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…( 18 , 31 ) In general, a quinone compound covalently forms adducts with thiol moieties; these reactions may be involved in the development of diseases or adaptation to stress. ( 32 ) We have reported that the pretreatment of SH-SY5Y cells with TD prevented cell death and suppressed intracellular ROS generation evoked by H 2 O 2 exposure. ( 33 ) This may occur because cells primed with TD upregulate the expression of the phase-II antioxidant enzymes NAD(P)H: quinone oxidoreductase 1 and heme oxygenase-1.…”
Section: Discussionmentioning
confidence: 99%
“…( 18 , 31 ) In general, a quinone compound covalently forms adducts with thiol moieties; these reactions may be involved in the development of diseases or adaptation to stress. ( 32 ) We have reported that the pretreatment of SH-SY5Y cells with TD prevented cell death and suppressed intracellular ROS generation evoked by H 2 O 2 exposure. ( 33 ) This may occur because cells primed with TD upregulate the expression of the phase-II antioxidant enzymes NAD(P)H: quinone oxidoreductase 1 and heme oxygenase-1.…”
Section: Discussionmentioning
confidence: 99%
“…The formed quinone could react with a thiol of the enzyme, resulting in the enzyme conjugation with the phytochemical (Fig. 4) [31]. Piceatannol is abundantly present in the fruit of Passiflora edulis [32] and is a metabolite of resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…The higher level of TPC in methanol extract than water extract, despite higher polarity of water, can also be related to the inhibitory action of methanol on the enzyme polyphenol oxidase [49] , which catalyzes two types of oxidative reactions: hydroxylation of monophenols to o-diphenols and oxidation of catechols to o-quinones, which are highly reactive compounds [50] . More importantly, o-quinones can easily combine with proteins to form insoluble complexes [51] .…”
Section: Phytochemical Analysismentioning
confidence: 99%